2022
DOI: 10.1002/ijfe.2694
|View full text |Cite
|
Sign up to set email alerts
|

Stock returns, government response strategies, and daily new case bursts during COVID‐19: A cross‐country perspective

Abstract: The purpose of the current research is to examine the influence of COVID‐19 pandemic related governmental policies and the bursts (e.g., drastic increases in cases during certain periods) of COVID‐19 cases on the abnormal returns of 725 hospitality and entertainment companies from the United States (US), China, the United Kingdom (UK), India, Thailand, Turkey, Mexico, and France. The study uses daily data from January 1, 2020, to November 20, 2021 and event study methodology. Our results offer the following in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Six studies report on low-income and middle-income countries (LMICs), specifically Thailand,32 Malaysia,33 Ethiopia,16 Poland,34 Czech Republic35 and the African Continental Free Trade Area (ACFTA) countries 36. Ten cross-country studies did not select a specific group of countries based on income 37–46. For example, one study looked at the stock volatility of 67 countries whose stock market data are reported by Datastream Global Equity Indices 45…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Six studies report on low-income and middle-income countries (LMICs), specifically Thailand,32 Malaysia,33 Ethiopia,16 Poland,34 Czech Republic35 and the African Continental Free Trade Area (ACFTA) countries 36. Ten cross-country studies did not select a specific group of countries based on income 37–46. For example, one study looked at the stock volatility of 67 countries whose stock market data are reported by Datastream Global Equity Indices 45…”
Section: Resultsmentioning
confidence: 99%
“…Most studies identified in our review focus on the effects of international travel restrictions implemented during early 2020 (n=12) 16 24 26 27 30 32 34–36 41 44 47. The second most studied is the intensity of ITMs in general, using the stringency index of travel measures from the Oxford Coronavirus Government Response Tracker (OxCGRT) 33 39 42 43 45.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations